Health practice among Muslim homebound older adults living in the Southern Thai community: An ethnographic study - Praneed Songwathana; Tippamas Chinnawong; Benjawan Ngamwongwiwat (Belitung Nursing Journal, 2023)
Background: Age-friendly environment helps promote older people’s health practices and healthy aging. However, little is known about health practices among those living at home in a Thai Muslim community. Objective: This study aimed to explore the health practices of Thai Muslim Homebound Older Adults (HOAs) in relation to their beliefs and experiences to maintain their holistic health. Methods: An ethnographic study design was used. Purposive and snowball sampling methods were used to select 15 HOAs as key informants, among whom nine were living in an urban area, and six were living in a rural area. Data were collected using in-depth interviews, participant observation, and field notes. Data were analyzed using thematic analysis. Results: Muslim HOAs performed their health practices culturally under the central theme of “Life and health are designated by God (Allah) for living with nature and comfort at their age.” The health practices consisted of four patterns: 1) Maintaining day-to-day functioning to stay independent, 2) Having a simple and comfortable life with support, 3) Performing religious activities as a priority of life for well-being, and 4) Managing symptoms to gain a balance and restore health. Conclusions: Understanding health practice patterns among HOAs would help nurses, especially primary care professionals, to promote healthy aging and independent living. In addition, culturally sensitive nursing care may be required to maintain the healthy living of Muslim older adults in the long term.